STUDENTS’ PERCEPTION OF LITERATURE AS A TEACHING STRATEGIES IN ENRICH THE EFL STUDENTS’ VOCABULARY - Rianyansa, Ari Andre; Maisarah, Ira (Indonesian Journal of Educational Development (IJED), 2024)
This study set out to find out what the students thought about using literature as a teaching approach to increase the vocabulary of EFL students. In order to learn what students think about using literature as a teaching approach to boost students' EFL vocabulary, this research employs interviews and a qualitative descriptive design. Thirty EFL students who were taught English at Universitas Islam Negeri Fatmawati Sukarno Bengkulu (UINFAS) are the participants in this study that consist of 9 male and 21 female students. Through stratified random sampling, they were chosen. Additionally, seven English lecturers from the Al-Ain district—two men and five women—were specifically selected to participate in the group interview. The data were analyzed quantitatively and qualitatively. Quantitative data were through percentage, frequency and mean scores, while qualitative data through thematic analysis. The interview findings revealed ten questioners of Literature. Based on the findings, because literature aided in the English teaching and learning process, most teachers were in favor of using it in the classroom. It indicates that the use of literature in EFL classrooms was well-received by the students.